Epidermolysis bullosa simplex with muscular dystrophy. Review of the literature and a case report - Kyrova, Jana (J Dermatol Case Rep, 2016)
BACKGROUND: Epidermolysis bullosa simplex associated with muscular dystrophy is a genetic skin disease caused by plectin deficiency. A case of a 19-year-old Czech patient affected with this disease and a review all previously published clinical cases are presented. MAIN OBSERVATIONS: In our patient, skin signs of the disease developed after birth. Bilateral ptosis at the age of 8 years was considered as the first specific symptom of muscular dystrophy. Since then, severe scoliosis, urological and psychiatric complication have quickly developed. The signs of plectin deficiency were found by histopathological studies, electron microscopy and antigen mapping of the skin and muscular samples. Two autosomal recessive mutations in the plectin gene leading to premature termination codon were disclosed by mutation analysis. By review of all published clinical cases, 49 patients with this disease were found. 54 different mutations in the plectin gene were published, p.(Arg2319*) in exon 31 being the most frequently found. Median age of muscular dystrophy development was 9.5 years. Hoarseness and respiratory complications were the most often complications beside skin involvement. CONCLUSION: Epidermolysis bullosa simplex with muscular dystrophy was diagnosed based on clinical, histopathological (skin and muscle biopsy) and mutation analysis of the plectin gene. Overview of the genetic and clinical characteristic of this disease could be presented by review of all previously published clinical cases.